PENINGKATAN PENYESUAIAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK - Tika Febriyani; Syaifuddin Latief; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2014)
The research aims to determine the increasing of student’s self-adjustment by group counseling class. The research method was quasi-experiment with one-group pretest-posttest design. The research subject was six students of grade X who had low self-adjustment at school. Data collecting technique used scale and observation. The research result showed that student’s self-adjustment increased after being given group counseling, it proved from the result of pretest and posttest which obtained Zoutput=-2.207 and Ztable 0.05= 0. ZoutputZtable, so that Ho was rejected and Ha was received, it meant that there is a difference with a significance level of 5% between the adjustment of students at the school before and after a given group counseling. The conclusion that there is an increasing on student’s self-adjustment by group counseling of the students grade X SMAN 9 Bandar Lampung.Tujuan penelitian ini untuk mengetahui peningkatan penyesuaian diri siswa melalui bimbingan kelompok. Metode penelitian ini adalah pre-experiment dengan one group pre-test post-test design. Subjek penelitian ini adalah enam siswa kelas X yang memiliki penyesuaian diri rendah di sekolah. Teknik pengumpulan data adalah skala dan observasi. Hasil penelitian menunjukkan penyesuaian diri siswa di sekolah meningkat setelah kegiatan bimbingan kelompok, hal ini ditunjukkan dari hasil pretest dan posttest yang diperoleh Zhitung = -2.207 Ztabel 0.05 = 0. ZhitungZtabel, maka Ho ditolak dan Ha diterima, artinya terdapat perbedaan dengan taraf signifikansi 5% antara penyesuaian diri siswa di sekolah sebelum dan setelah diberikan bimbingan kelompok. Kesimpulannya adalah terdapat peningkatan penyesuaian diri siswa di sekolah setelah diadakannya bimbingan kelompok pada siswa kelas X SMA Negeri 9 Bandar Lampung.Kata kunci : bimbingan dan konseling, bimbingan kelompok, penyesuaian diri